United States monetary policy: its contribution to prosperity without inflation; background papers prepared for the use of participants, and the Final report of the Fourteenth American Assembly, Arden House, Harriman Campus of Columbia University, Harriman, New York, October 16-19, 1958 - American Assembly (New York : American Assembly., 1958)
This book examines the role of monetary system in the United States economy, the monetary problems and policies aimed at addressing it.
Bibliographical footnotes.
usc 20/09/18
Loans
Keywords: Currency question